Developmental neurotoxicity of an anatoxin-a-producing cyanobacteria (Aphanizomenon gracile) lysate to zebrafish (Danio rerio) - Liu, Chang; Cui, Baiyu; Hu, Lian; Li, Rui; Xiao, Peng; Zuo, Jun; Wang, Zeshuang; Ma, Zengling; Fan, Yuping; Zhang, He; Li, Renhui (Frontiers in Microbiology, 2025)
Harmful cyanobacterial blooms occur frequently worldwide with serious environmental impacts. Many detrimental cyanobacteria are well known for their potential to synthesize various cyanotoxins, posing significant threats to aquatic ecosystems and public health worldwide. While most studies focus on the toxicological impacts of microcystins and its main producer Microcystis aeruginosa, the ecotoxic effects of anatoxin-a and anatoxin-a-producing cyanobacteria are not fully understood. This study investigated the response of zebrafish (Danio rerio) to a ruptured cell solution (RCS) of a planktonic anatoxin-a-producing Aphanizomenon gracile. The RCS exposure negatively affected the hatching of zebrafish embryos, and promoted malformation. Furthermore, RCS treatment also disrupted neurobehaviors, and induced severe oxidative stress. In addition, the RCS inhibited the activity of acetylcholinesterase, and dysregulated the expression of several genes related to neuron-development and activated apoptosis in zebrafish. These results suggest that blooms of anatoxin-a-producing Aphanizomenon gracile will have neurotoxic effects on aquatic animals, and could impact human health. They help to further understand the potential neurotoxicity of harmful cyanobacteria, and highlight the need for further studies and risk assessments of the ecological impacts of harmful cyanobacterial blooms in freshwater ecosystems.